PERANAN KADER PEMBERDAYAAN MASYARAKAT DESA (KPMD) DAN PARTISIPASI MASYARAKAT PADA PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PERDESAAN (PNPM-MP) DI KECAMATAN WONOSOBO KABUPATEN TANGGAMUS - Andika Rismayanti Hadi; Irwan Effendi; Tubagus Hasanuddin (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2013)
The objectives of this research were to find out: 1) the roles of Village Community Empowerment Workers(KPMD) in National Program of Autonomous Village Community Empowerment (PNPM-MP);2) communityparticipation levels in National Program of Autonomous Village Community Empowerment; and 3)correlation between the roles of the KPMD in the PNPM-MP and their participation. This research wasconducted from July to August 2012. Respondents were 12 Workers of Village Community Empowermentand 60 poor families taken by using disproportional stratified random sampling. This was a surveyresearch. The correlations between variables were tested by using Rank Spearman. The results showedthat: 1) level of the roles of the KPMD was in high category in facilitating village meetings, ensuring stepsin program activities, encouraging and ensuring program principles and policy implementations, followingmonthly meetings with Field Assistant, and encouraging community to participate in conducting activities.However, level of role of Village Community Empowerment Worker (KPMD) in disseminating andsocializing programs were in middle category; 2) the community participation level on planningdevelopment, making decision, monitoring, evaluating program activity, and taking advantages ofdevelopment results were in high category. However, the community participation level in the program werelow category and the community participation level in providing autonomous resources were low; 3) therewas a significant correlation between the roles of KPMD and community participation level in the PNPMMPprogram in Wonosobo sub district of Tanggamus Regency.